Occupational exposure to hexavalent chromium: biomarkers of genotoxicity in human peripheral blood - Afonso, Catarina Maia (2021)
The hexavalent Chromium [Cr(VI)] is a human carcinogen, which is still authorized for use in several industrial settings because it has been difficult to replace. This was the reasoning to select it as a priority chemical by the European Human Biomonitoring Initiative (HBM4EU, https://www.hbm4eu.eu/), which aims to bridge chemicals human exposure to their possible impact on health. For that purpose, not only exposure was evaluated, but also early effect biomarkers were done to reflect potential health outcomes in several countries across Europe. In Portugal, the study was developed in one aircraft maintenance company since the substitution of Cr(VI) is not expected in the near future. Following the company agreement and the volunteers informed consent, an individual questionnaire was filled in order to obtain personal information, as well as lifestyle habits and occupational issues. Personal air samples were collected in order to assess occupational exposure to Cr(VI) soluble and insoluble compounds. Sampling for effect biomarkers analyses involved blood samples from 50 workers and 26 healthy individuals (controls). Biomarkers of effect involving the analysis of chromosome alterations (micronucleus assay) and DNA damage (comet assay) were studied; the results were statistically compared. Cr(VI)-exposed workers display a significantly higher frequency of micronucleated binucleated cells (p < 0.001) and an increased level of DNA breaks (comet assay) (p < 0.001) when compared with the non-exposed group. Only in the workplaces dedicated to painting exterior surfaces the values (0.4 mg/m3) were higher than the Occupational Exposure Limit (OEL of 0.010 mg/m3) currently proposed by the Directive (EU) 2019/130, 16/01/2019. The present results suggest a potential health risk for this group of workers given that an association between an increased micronucleus frequency and cancer risk has been shown. Also, these findings should promote the investment in new risk management measures and the effective application of the ones already in place, such as adequate local ventilation and a frequent use of protective equipment.